THE DEVELOPMENT OF SCIENCE AND TECHNOLOGY AND ITS IMPACT ON HUMAN MORAL LIFE - Darwin Effendi (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2018)
The development of science and technology is progressing in accordance with the demands of the times. Technological users if not wise will damage the life of human life itself. The use of technology that is notbalanced with qualified Human Resources will cause problems. The purpose of writing in this paper is to describe the impact of the development of science and technology on human moral life. Descriptive method with library research used in writing this paper. The results of the analysis of the development of science and technology to human moral life, namely (1) the field of information and communication, the development of science and technology allows people more quickly get the information accurately and latest in this hemisphere through the internet, However, the use of the internet abused by opening porn sites; (2) the field of education, the development of the use of media technologies such as LCD which facilitate the process of teaching and learning, the proliferation of mass media, both print and electronic as well as online adds a source of knowledge for students. However, non-educating soap opera shows in electronic media can damage students' morale; (3) the economic field, the growth of the economy with emerging industrial products that produce labor-power; (4) social and cultural fields, technological advancements allow the entry of foreign cultures that can add to the nuances of local culture and mutual cooperation to improve the cultural and social relations between countries.The negative impact of technological advancement on the rise of juvenile delinquency such as brawl, scratching in public places to crime because of culture gotong-royong and help-help, and manners as the nation's cultural products increasingly thinning among teenagers.Keywords: science and technology, morals